Synthesis of xLiMnPO4·yLi3V2(PO4)3/C Nanocomposites for Lithium Ion Batteries Using Tributyl Phosphate as Phosphor Source - Yanming Wang; Bo Zhu; Xiaoyu Liu; Fei Wang (Journal of Nanotechnology)
The xLiMnPO4·yLi3V2(PO4)3/C (x/y = 1 : 0, 12 : 1, 8 : 1, 6 : 1, 4 : 1, 0 : 1) composite cathode materials are synthesized using tributyl phosphate as a novel organic phosphor source via a solid-state reaction process. All obtained xLiMnPO4·yLi3V2(PO4)3/C composites present similar particles morphology with an average size of ca. 100 nm and low extent agglomeration. The electrochemical performance of pristine LiMnPO4/C can be effectively improved by adding small amounts of Li3V2(PO4)3 additives. The 4LiMnPO4·Li3V2(PO4)3/C has a high discharge capacity of 143 mAh g−1 at 0.1 C and keeps its 94% at the end of 100 cycles.